2016
DOI: 10.1186/s12906-016-1342-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute and subacute toxicity of an ethanolic extract of Melandrii Herba in Crl:CD sprague dawley rats and cytotoxicity of the extract in vitro

Abstract: BackgroundMelandrii Herba, a medicinal plant, has been used in Korea for treatment of bacterial and fungal infection. However, the safety and toxicity of Melandrii Herba have not yet been established. Therefore, we investigated the acute and subacute toxicity of an ethanolic extract of Melandrii Herba (MHEE) in Crl:CD Sprague Dawley rats and cytotoxicity of MHEE in vitro.MethodsTo study acute toxicity, rats were treated with MHEE at single doses of 0, 500, 1000, and 2000 mg/kg administered by oral gavage, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Moreover, we observed that treatment with ME by itself demonstrated no cytotoxicity effect on SH-SY5Y cell viability ( Figure 1 ). This observation is consistent with previous reports stating that oral doses of ME of up to 2000 mg/kg had no toxicity in vivo [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, we observed that treatment with ME by itself demonstrated no cytotoxicity effect on SH-SY5Y cell viability ( Figure 1 ). This observation is consistent with previous reports stating that oral doses of ME of up to 2000 mg/kg had no toxicity in vivo [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…Animal handling was done in line with the procedures outlined by the National Agency of Drug and Food Control of Indonesia No. 7 of 2014 [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The amount of crude protein, crude fat, crude fiber, ash, Ca, and P was 18, 5, 5, 8, 0.85, and 0.70%, respectively, in the supplied lab diet. To observe the toxic effects of test materials, subacute in vivo toxicity tests were conducted for 28 days [21]. Based on the observations regarding the highest dose of ammonia without effect reported by Tuleka et al, pre-treated struvite doses of 1 and 10 mg kg −1 BW were designated to evaluate the repeated dose toxicity [22].…”
Section: Methodsmentioning
confidence: 99%